Math Anxiety and Achievement: Investigating Parent-Child Relationships in the Homework-Helping Context - DiStefano, Gosselin Michela (Université d'Ottawa / University of Ottawa, 2024)
This dissertation investigated the multifaceted dynamics of parent-child interactions during math homework help and their influence on children's achievement and anxiety towards math. Across three studies - using Social Learning Theory, Social Referencing Theory, and Attachment Theory as theoretical frameworks - the way in which both child and parent math anxiety relate to interactions during math homework-help, emotional experiences, math achievement, and the quality of parent-child attachment was explored. Study 1 was conducted over two separate studies to explore the connection between parents' math anxiety and their perceptions of math homework-helping interactions. Surveys conducted with parents of children in grades 1 to 6 across North America (Study 1a [n = 192]: controlling for math knowledge; Study 1b [n = 214]: controlling for math knowledge and general anxiety) revealed that higher math anxiety was associated with an altogether more negative homework-helping experience from the parent's perspective (i.e., diminished confidence, increased conflict, stress, frustration, and emotional distance during math homework interactions). Building upon these results, Study 2 used a multi-method approach to assess the quality of math homework-helping interactions, including observational coding methods. The study involved 40 Canadian parents and their children (ages 10-12 years; grades 5 to 7) engaging in a simulated math homework task. Results indicated that higher quality interactions correlate with task accuracy, and the variability in the quality of the interaction is linked to parents' and children's math achievement, as well as children's math anxiety. The linguistic analysis revealed a positive correlation between parents' and children's use of negative words during the interaction. Additionally, the variability in the frequency of positive words used by parents was associated with parents' math achievement and accuracy on the math task. Using the same sample as Study 2, Study 3 extended beyond the homework-helping context by investigating the relation between parent-child attachment, math homework-helping interactions, math achievement, and math anxiety. Attachment security and the quality of the simulated math task interaction were found to be marginally correlated, while attachment insecurity was found to be associated with lower quality interactions during the simulated math task, as well as increased math anxiety in children. Taken together, these studies provide valuable insights into the influence of parent-child interactions on children's mathematical well-being, substantiated by both self-reported data and observational methods. The findings from this dissertation underscore the importance of adopting a more holistic approach that integrates the quality of parent-child relationships with individual cognitive and emotional factors. This approach is essential for gaining a deeper understanding of children's experiences with mathematics.
Keywords: math anxiety; math achievement; homework; parental involvement; parent-child interactions; parent-child attachment; mathematical well-being